2012
DOI: 10.4269/ajtmh.2012.11-0625
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes among Patients with Sickle Cell Disease at Korle-Bu Teaching Hospital, Accra, Ghana: Retrospective Cohort Study

Abstract: Abstract. Pregnancy in sickle cell disease (SCD) patients is associated with increased risk of maternal and fetal mortality. This study determines pregnancy outcomes among women with SCD delivering at Korle-Bu Teaching Hospital, Accra, Ghana. Nine hundred sixty (960) medical records of pregnant women (131 HbSS, 112 HbSC, and 717 comparison group) from 2007 to 2008 were reviewed. The HbSS women were at increased risk of eclampsia (adjusted odds ratio [AOR] = 10.56, 95% confidence interval [CI] = 3.60-30.96, P 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
68
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 48 publications
12
68
2
6
Order By: Relevance
“…But, unlike reported earlier, GDM and was comparable with normal population. 15,17 As previously reported, present study showed a 100% incidence of moderate to severe anemia in HbSS antenatal women; while there were studies with anemia as less as 8.4%. 9,22,17 But we found anemia in only 46.88% of HbAS women as against the 95% in earlier reports.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…But, unlike reported earlier, GDM and was comparable with normal population. 15,17 As previously reported, present study showed a 100% incidence of moderate to severe anemia in HbSS antenatal women; while there were studies with anemia as less as 8.4%. 9,22,17 But we found anemia in only 46.88% of HbAS women as against the 95% in earlier reports.…”
Section: Discussionsupporting
confidence: 79%
“…9,15 Similar to many other studies, we found that obstetric complications like preeclampsia and gestational hypertension were high in women with sickle cell disease with a higher risk in homozygous (HbSS) genotype. [9][10][11][15][16][17][18][19] Eclampsia which is a life threatening complication of preeclampsia was reported to be 10 times high in HbSS women. 17 This study also showed a higher incidence of eclampsia in consistent with an earlier metaanalysis and also reports from other states of India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the 21 studies included in the meta-analysis are outlined in Table 2 (HbSS disease [12][13][14][15][16][17][18][19][20][21][22][23] ), Table 3 (HbSC disease 6,17,18,20,23 ), and Table 4 (SCD with genotype not specified). [24][25][26][27][28][29][30][31] All studies were categorized as pregnancy cohort studies.…”
Section: Study Characteristicsmentioning
confidence: 99%